Assessment of Plasma Sodium to Potassium Ratio, Renal Function, Markers of Oxidative Stress, Inflammation, and Endothelial Dysfunction in Nigerian Hypertensive Patients - Oloruntoba A. Ekun; Folasade Daniel; Philip Adebola; Adeola Ajibare; Oyeronke O. Ekun; Oluwafunso O Omogoroye; Oluwafemi S. Ilori; Bankole J. Oluwasayo; Mary F. Oshundun; Sade R. Oyegbami (International Journal of Hypertension)
Background. This study investigated plasma sodium/potassium ratio, markers of oxidative stress, renal function, and endothelial dysfunction in hypertensive Nigerians. Materials and Methods. Five hundred forty-nine volunteers consisting of three hundred and twenty-four hypertensive and two hundred twenty-five controls participated in this study. Blood samples were collected from the participants and were analyzed for electrolytes, markers of oxidative stress, endothelial dysfunction, renal function, and inflammation, using ion-selective electrodes, spectrophotometric, and enzyme-linked immunosorbent assay methods, respectively. Results. The mean systolic blood pressure, mean diastolic blood pressure, mean arterial blood pressure, and body mass index (BMI) were significantly elevated among the hypertensive group when compared with control (p<0.001). The mean sodium increased, while potassium and bicarbonate (HCO3−) decreased (p<0.001) in hypertensive volunteers. The sodium-potassium ratio (Na+/K+) and urea were raised (p<0.001) in the hypertensive group when compared with the control. Glutathione, superoxide dismutase, nitric oxide (NO), and catalase were significantly reduced (p<0.001) while malondialdehyde (MDA), high-sensitivity C-reactive protein (hs-CRP), and ferritin were raised significantly (p<0.001) in hypertensive participants. The odds of hypertension and its complications increased (p<0.001) with an increase in BMI, Na+/K+, hs-CRP, MDA, and ferritin and a decrease in estimated glomerular filtration rate (eGFR), glutathione, superoxide dismutase, and catalase. Conclusion. An increase in Na+/K+, urea, hs-CRP, ferritin, MDA, and BMI and a decrease in eGFR, glutathione, and superoxide dismutase were associated with an increased risk of hypertension complication. Abnormal values of markers of oxidative stress, inflammation, and endothelial function could impact deleterious effects on the cardiovascular system among hypertensive Nigerians. A decreased bicarbonate possibly suggests an occult acid-base imbalance among hypertensive volunteers.